TINGKAT KEPUASAN PETERNAK PADA USAHA PETERNAKAN SAPI POTONG DI KABUPATEN BANYUMAS - F. H. R., AT-TALUQY; MUATIP, K.; WAKHIDATI, Y. N. (Majalah Ilmiah Peternakan; Vol 27 No 3 (2024): Vol. 27 No. 3 (2024)DO - 10.24843/MIP.V27.i03.p04, 2024)
The study aimed to analyse the effect of education, length of farming, and number of livestock on the satisfaction level of beef cattle farmers in Banyumas Regency based on income and access to information. The research was con- ducted using the survey method. The sample size was determined using the Slovin formula with a margin of error of 10% with a total of 81 respondents. Data analysis used descriptive analysis and logistic regression analysis. The results of descriptive analysis showed that most farmers had completed primary school (55.55%), farming duration <10 years (49.38%), and number of livestock <5 heads (86.41%). The satisfaction level of farmers was in the dissa- tisfied (72.83%) and satisfied (27.16%) categories. The results of logistic regression analysis showed that the level of education (0.006) had a significant effect on the level of farmer satisfaction, while the length of farming (0.131) and the number of livestock (0.599) had no significant effect on the level of farmer satisfaction.